KUALITAS PELAYANAN ADMINISTRASI UMUM DI KANTOR KECAMATAN PALU TIMUR KOTA PALU - Muftia, Itma; Susanti, Ani; Rachmad (JPS: Journal of Publicness Studies, 2025)
This study aims to determine how the quality of administrative services at the East Palu District Office of Palu City. The basis of this research is descriptive qualitative with 5 informants. Data collection techniques through informants accompanied by observation, interviews and documentation. The theory used in this study Ndraha (1999: 63) uses 4 dimensions including aspects of speed, accuracy, convenience and fairness. Based on the results of the study, administrative services in the sub-district office of the eastern hammer city of hammer city as a whole the results of each dimension of research based on theory have been categorized as pretty good. However, there are two aspects that are good, namely the accuracy dimension and the justice dimension, while there are aspects that are not good, namely the speed dimension and the convenience dimension. This is because the level of awareness of employees is still lacking so that it can be seen from, for example, facilities and infrastructure that are not fully supportive and also because of the lack of attention of employees to facilitate the collection of file requirements in management. Therefore, administrative services have not been very effective because all dimensions have not been maximized by the elements responsible for administrative services at the sub-district office of east hammer city.